Simultaneous Observation of Two Isolated Proton Auroras at Subauroral Latitudes by a Highly Sensitive All‐Sky Camera and Van Allen Probes. Issue 5 (21st May 2021) - Nakamura, Kohki; Shiokawa, Kazuo; Otsuka, Yuichi; Shinbori, Atsuki; Miyoshi, Yoshizumi; Connors, Martin; Spence, Harlan; Reeves, Geoff; Funsten, Herbert O.; MacDowall, Robert; Smith, Charles; Wygant, John; et al.
Abstract: Isolated proton auroras (IPAs) appearing at subauroral latitudes are generated by energetic protons precipitating from the magnetosphere through interaction with electromagnetic ion cyclotron (EMIC) waves. An IPA thus indicates the spatial scale and temporal variation of wave‐particle interactions in the magnetosphere. In this study, a unique event of simultaneous ground and magnetospheric satellite observations of two IPAs were conducted on March 16, 2015, using an all‐sky imager at Athabasca, Canada and Van Allen Probes. The Van Allen Probes observed two isolated EMIC waves with frequencies of ∼1 and 0.4 Hz at L ≈ 5.0 when the satellite footprint crossed over the two IPAs. This suggests that the IPAs were caused by localized EMIC waves. Proton flux at 5–20 keV increased locally when the EMIC waves appeared. Electron flux at energies below ∼500 eV also increased. Temperature anisotropy of the energetic protons was estimated at 1.5–2.5 over a wide L ‐value range of 3.0–5.2. Electron density gradually decreased from L = 3.5 to 5.4, suggesting that the EMIC wave at L ≈ 5.0 was located in the gradual plasmapause. From these observations, we conclude that the localized IPAs and associated EMIC waves took place because of localized enhancement of energetic proton flux and plasma density structure near the plasmapause. The magnetic field observed by the satellite showed small variation during the wave observation, indicating that the IPAs were accompanied by the weak field‐aligned current. Plain Language Summary: Isolated proton aurora (IPA) appearing at subauroral latitudes (∼55°–65°) is generated by energetic protons precipitating from Earth's magnetosphere, possibly through interaction with plasma waves called electromagnetic ion cyclotron (EMIC) waves. The IPA indicates the spatial scale and temporal variation of wave‐particle interactions in the magnetosphere. EMIC waves are expected to contribute to the rapid loss of radiation‐belt particles into the atmosphere. Thus, IPAs present essential information related to EMIC waves. In this study, we report unique simultaneous ground and magnetospheric satellite observations of two IPAs using an all‐sky imager at Athabasca, Canada and Van Allen Probes acquired on March 16, 2015. Van Allen Probes observed two isolated EMIC waves with frequencies of ∼1 and 0.4 Hz when the satellite footprint crossed over the two IPAs. This indicates that the IPAs were caused by localized EMIC waves. We conclude that the localized IPAs and associated EMIC waves took place due to localized enhancement of energetic proton number flux and local plasma density structure near the plasmapause. Key Points: We report unique simultaneous ground and magnetospheric satellite observations of two isolated proton auroras at subauroral latitudes Van Allen Probes observed two EMIC waves at ∼1 and 0.4 Hz during crossings of the isolated proton auroras When the EMIC waves were observed, 5–20 keV proton flux was locally enhanced near a steep density decrease in the plasmapause region